2020
DOI: 10.7554/elife.57246
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 latent reservoir is largely sensitive to circulating T cells

Abstract: HIV-1 specific CD8+ T cells are an important component of HIV-1 curative strategies. Viral variants in the HIV-1 reservoir may limit the capacity of T cells to detect and clear virus-infected cells. We investigated the patterns of T cell escape variants in the replication-competent reservoir of 25 persons living with HIV-1 (PLWH) durably suppressed on ART. We identified all reactive T cell epitopes in the HIV-1 proteome for each participant and sequenced HIV-1 outgrowth viruses from resting CD4+ T cells. All n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 111 publications
(168 reference statements)
5
18
0
Order By: Relevance
“…44 This faster rate of clearance could also be due to the lower proportion of cytotoxic T lymphocyte escape mutations in the reservoir of these participants compared with those treated later; 45 although, this factor remains controversial. 46 As reported in our study, levels of integrated HIV DNA declined less rapidly than levels of total HIV DNA and 2-LTR circles, 14,19,47 indicating that unintegrated HIV genomes are more labile, possibly because they are diluted by T-cell proliferation.…”
Section: Discussionsupporting
confidence: 63%
“…44 This faster rate of clearance could also be due to the lower proportion of cytotoxic T lymphocyte escape mutations in the reservoir of these participants compared with those treated later; 45 although, this factor remains controversial. 46 As reported in our study, levels of integrated HIV DNA declined less rapidly than levels of total HIV DNA and 2-LTR circles, 14,19,47 indicating that unintegrated HIV genomes are more labile, possibly because they are diluted by T-cell proliferation.…”
Section: Discussionsupporting
confidence: 63%
“…When % inhibition was then calculated using Equation (1), we observed that all HIVART participants produced a positive (> 0%) virus inhibition (n=14, range: 8.2% to 73.3% inhibition), consistent with our previous reports that HIVART participants maintain functional HIV-specific CD8 T cells over time ( 16 , 23 ) ( Figure 3B ). The level of inhibition in HD was mostly negative (n=21, mean: -13.7%, range: -49.9 to 20.9%), though some participants produced % inhibition > 0%, suggesting false positives or non-specific CD8 T cell mediated virus inhibition ( Figure 3B ).…”
Section: Resultssupporting
confidence: 88%
“…However, the question at hand pertains to HIV-specific T cell responses that show evidence of being maintained by recent antigen recognition, indicating that they target epitopes that are intact in at least a portion of the reservoir. Further supporting this idea are the previous observations that (a) the fixation of escape mutations leads to the contraction of corresponding T cell responses ( 51 ) and (b) the substantial majority of HIV-specific T cells that remain detectable after years of ART target epitopes for which escape is not fixed in corresponding reservoir viruses ( 52 , 53 ). As with latency, our data do not lead us to contest the idea that the fixation of escape mutations in the reservoir diminishes the overall potential for immune recognition or the value of therapeutic strategies to address either of these limitations.…”
Section: Discussionmentioning
confidence: 55%